LEGAL ANALYSIS OF THE RESPONSIBILITY OF PERPETRATORS OF THE CRIMINAL ACT OF THEFT WITH VIOLENCE RESULTING IN DEATH IN A DUALISTIC PERSPECTIVE - Ardiansyah, Nico (Jurnal Hukum Khaira Ummah, 2024)
Indonesia is a country of law, so all aspects of state administration and management are regulated by a system of laws and regulations. Criminal acts and crimes in human life are social phenomena faced by every person and even every country at all times. Theft is one of the crimes that often occur in society. This thesis aims to analyze the construction of the crime of theft with aggravating violence resulting in death and the implementation of criminal responsibility for perpetrators of the crime of theft with violence resulting in death in the perspective of the dualistic conception. The approach method used in this study is a normative legal approach. The research specifications used are descriptive analysis, primary and secondary data sources and this study will be processed using qualitative analysis. The problem is analyzed using the theory of Legal Certainty, criminal liability, and Piana's Accountability theory. Based on the research results, the construction of the crime of theft with violence resulting in death in the concept of legal certainty is regulated in Article 365 paragraph 4 of the Criminal Code. A trial process ends with the passing of a final decision (verdict) in which there is still a criminal sentence (punishment) against the guilty defendant and in that decision. Criminal liability for the perpetrators involved in the crime of fraud in Decision Number 8 / Pid.B / 2024 / PN Mgg has fulfilled the value of criminal liability in accordance with the provisions of the actus because the defendants have committed prohibited acts in accordance with those contained in Article 365 paragraph 4 of the Criminal Code. Then in accordance with the provisions of mens rea which is due to the existence of evil intentions that can be seen or have been proven by the Panel of Judges in the trial. So these two elements have been fulfilled, then criminal liability arises so that based on these provisions the defendant must be responsible for his actions by undergoing a sentence or criminal sanction.